Study on Clinical and Histopathological Changes of Alopecia Areata (Medicine Today, 2018)
Alopecia areata is a common, unpredictable, nonscarring form of hair loss. It is characterized by rapid and complete loss of hair in one or more round or oval patches, usually on the scalp, bearded area, eyebrows, eyelashes and less commonly on other hairy areas of the body. The present study was undertaken in the department of Dermatology and Venereology of Ibn Sina Medical College, Dhaka from July 2014 to June 2015 to observe the histopathological changes in different stages of alopecia areata. For this purpose 30 patients with age ranged from 18 to 45 years were enrolled. Of them 17 were males and 13 were females. A 4 mm punch biopsy from the involved scalp taken from each patient and histopatological changes were examined. The study revealed that anagen hairs decreased but catagen and telogen hair increased in all stages of alopecia areata. Telogen hairs increased in acute and chronic stage and catagen hair increased markedly in subacute stage. Although miniaturized (atrophic) follicle was frequently found in chronic stage. It was absent in acute and subacute stages. Moderate to dense peribulbar infiltration of lymphocytes were observed in acute stage and mild to moderate infiltration in subacute stage. In chronic stage either no or mild infiltrations were observed. Peribulbar infiltration of eosinophils and macrophages was seen in all stages of alopecia areata. Thus we can conclude that alopecia areata can be diagnosed with some confidence, even when inflammatory infiltrate is absent, based on increasing numbers of telogen hairs in the acute and subacute stages and increasing miniaturized hairs in chronic stage.Medicine Today 2018 Vol.30(1): 30-33